ULTRASI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN LITERASI DAN NUMERASI SISWA SD UPT NEGERI 064983 MEDAN - Sihombing, Imelda; Saragi, Charmelita (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
The snakes and ladders game is a game that is commonly found in everyday life. Although nowadays the use of technology is excellent for children. However, the game of snakes and ladders still exists. The snakes and ladders game is one of the games that can be used as learning media in schools. ULTRASI Literacy and Numeracy Snakes and Ladders is one example. The objectives of this ULTRASI activity include (1) Developing and implementing traditional games as learning media so that they are still recognized by children and (2) Improving students' literacy and numeracy skills. The steps of the ULTRASI activity at SD Negeri 064983 Gaperta include: (1) preparation stage, in the preparation stage of the ULTRASI game there are several things that are prepared including the game board, question cards related to literacy and numeracy, answer cards and dice. Students were also given a pre-test. The game board was printed on a 2 x 1.5 m banner. (2) Implementation stage. In the implementation stage, students in class V-A and class V-B formed groups of 6-7 people each, each team alternately rolled the dice and one representative walked on the game board according to the dice, each time they stopped at the challenge, the students would take a question card and answer the question. If the answer is wrong then the student will retreat a number of dice earlier. And so on. (3) Evaluation stage. At this stage students are given literacy and numeracy questions as a post-test. This ULTRASI activity was carried out with the guidance of the 7th batch of Teaching Campus students who served at SD Negeri 064983 Gaperta. The participants of the Snakes and Ladders game were students in grades V-A and V-B, totaling 66 people. The results obtained that the snakes and ladders game went well. Students were happy and excited. The post-test results obtained that the average literacy and numeracy skills of students increased.